2011
DOI: 10.4103/0975-5950.94488
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic third molar in the maxillary sinus

Abstract: Ectopic eruption of teeth into a region other than the oral cavity is rare although there have been reports of teeth in the nasal septum, mandibular condyle, coronoid process, palate, chin and maxillary sinus. Occasionally, a tooth may erupt in the maxillary sinus and present with local sinonasal symptoms attributed to chronic sinusitis. We present a case of an ectopic maxillary third molar tooth that caused chronic purulent sinusitis in relation to the right maxillary sinus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 7 publications
0
18
0
1
Order By: Relevance
“…When a dentigerous cyst invades the maxillary sinus, the related symptoms usually develop late in the process, possibly involving facial pain and swelling, paraesthesias, headache, nasal stuffiness, obstruction of the sinus and even blindness.…”
Section: Introductionmentioning
confidence: 99%
“…When a dentigerous cyst invades the maxillary sinus, the related symptoms usually develop late in the process, possibly involving facial pain and swelling, paraesthesias, headache, nasal stuffiness, obstruction of the sinus and even blindness.…”
Section: Introductionmentioning
confidence: 99%
“…Este fato pode ser relacionado ao fato das imagens utilizadas neste estudo serem de arquivo de Instituição de Ensino, que configura referência para encaminhamento de patologias e variações de anatomia, a fim de receberem tratamento adequado.A presença de raízes acessórias ou supranumerárias é um acometimento raro, mas seu significado é essencial para sucesso de tratamentos empregados seja tratamento pulpar ou extração de dentes, pois podem representar dificuldades clínicas especialmente quando elas não estão previstas20 . Tanto dentes decíduos quanto os permanentes podem apresentar esta variação 23 e baixa prevalência24 .CONCLUSÃOPela análise dos dados coletados podemos concluir que a prevalência de variações anatômicas em dentes permanentes é baixa, porém não rara, sem distinção entre os gêneros, mas de significado clínico por induzir, em algumas situações, o comprometimento pulpar ou dificultar terapias odontológicas.…”
unclassified
“…If left untreated, the ectopic tooth has the tendency to form a cyst or tumor and/or the lesion may cause perforation of the orbital floor and obliteration of the nasal cavity. Mohan et al (17) reported that they treated a case of ectopic tooth, which was the cause of recurrent sinusitis and purulent rhinorrhea in spite of administering antibiotics repeatedly, by Caldwell-Luc procedure. In conclusion, the dental originated foreign bodies are the most common observed ones among those located in maxillary sinus.…”
Section: Discussionmentioning
confidence: 99%